Large-area fabrication of TiN thin films with photothermal effect via PECVD. Issue 6 (15th April 2020) - Ge, Wanyin; Chang, Zhe; Siddique, Awais; Shi, Bo; Liu, Chun
Abstract: Titanium nitride alloy has triggered extensive interests for the actual application in aeronautics and astronautics, especially in the biological window serving as cancer therapy and tumor detection due to broad band absorption. However, developing a facile and reliable method for the manufacture of TiN films is still a propelled and demanding challenge. Here we present a one-step approach to obtain cubic-TiN films using plasma-enhanced chemical vapor deposition (PECVD) for the first time. Large-scale TiN films can be deposited on sophisticated substrate ( e.g. flattened and curled shape) with controllable size by our PECVD approach. The chemical composition and structural analysis were conducted by X-ray diffraction, scanning electron microscope, transmission electron microscopy, and X-ray photoelectron spectroscopy. Furthermore, the TiN powders extracted from our films for photothermal effect demonstrated an excellent photothermal conversion efficiency of 47.9% under 808 nm irradiation. Our study not only offers a facile PECVD route to realize the TiN films on sophisticated substrates, but also provides a promising candidate for photothermal therapy in the future.